Barreiras que limitam a logística reversa de resíduos de equipamentos eletroeletrônicos das instituições de ensino superior na cidade de São Paulo - Schroeder, Adriano Michelotti (2017)
Electrical and Electronic Equipment have become present in the daily life of people and enterprises. Due to technologies breakthrough that make easier the interconnection of those equipment, regardless of distance, manufacturers, types of models and used operational systems, those equipments have become even more essential, such of being the main factor of changing routines and enterprises processes, extending to the people. Nevertheless, the process of teaching and learning in basic schools and universities has also started to use informatics as a powerful tool, which students can visualize relevant aspects of the subjects through software applications, simulators, immersed in virtual environments, but, very close of reality. However, as those environments require hardware and software compatible with actual informatics scene, the problem of fast obsolescence tends to be more evident, as these new virtual environments require greater computing resources. Those frequent updates of those equipments contribute to make educational institutions to be a potential generator of Waste of Electrical and Electronic Equipments, a kind of waste that demands specifics procedures to correct disposal, to prevent environment and people harm. Therefore, it is natural to set up some obstacles to make the process of correct disposal more difficult, which define the focus of this work, followed by main objective to identify all of those barriers. As benefits, all results of this work will be available to guide future studies to reach out some new appropriate ways to managing and disposal of those kind of wastes, considering minimum financial, social and environmental impacts for educational institutions in São Paulo city.